Ancestry of the Timorese: age-related macular degeneration associated genotype and allele sharing among human populations from throughout the world - Morrison, Margaux A.; Magalhaes, Tiago R.; Ramke, Jacqueline; Smith, Silvia E.; Ennis, Sean; Simpson, Claire L.; Portas, Laura; Murgia, Federico; Ahn, Jeeyun; Dardenne, Caitlin; Mayne, Katie; Robinson, Rosann; et al. (Frontiers in Genetics, 2015)
We observed that the third leading cause of blindness in the world, age-related macular degeneration (AMD), occurs at a very low documented frequency in a population-based cohort from Timor-Leste. Thus, we determined a complete catalogue of the ancestry of the Timorese by analysis of whole exome chip data and haplogroup analysis of SNP genotypes determined by sequencing the Hypervariable I and II regions of the mitochondrial genome and 17 genotyped YSTR markers obtained from 535 individuals. We genotyped 20 previously reported AMD-associated SNPs in the Timorese to examine their allele frequencies compared to and between previously documented AMD cohorts of varying ethnicities. For those without AMD (average age > 55 years), genotype and allele frequencies were similar for most SNPs with a few exceptions. The major risk allele of HTRA1 rs11200638 (10q26) was at a significantly higher frequency in the Timorese, as well as 3 of the 5 protective CFH (1q32) SNPs (rs800292, rs2284664, and rs12066959). Additionally, the most commonly associated AMD-risk SNP, CFH rs1061170 (Y402H), was also seen at a much lower frequency in the Korean and Timorese populations than in the assessed Caucasian populations (C ~7% vs. ~40%, respectively). The difference in allele frequencies between the Timorese population and the other genotyped populations, along with the haplogroup analysis, also highlight the genetic diversity of the Timorese. Specifically, the most common ancestry groupings were Oceanic (Melanesian and Papuan) and Eastern Asian (specifically Han Chinese). The low prevalence of AMD in the Timorese population (2 of 535 randomly selected participants) may be due to the enrichment of protective alleles in this population at the 1q32 locus.